Potential effects of climate change on northwest Portuguese coastal zones - Carlos Coelho (2009)
Coastal erosion is a common problem in Europe; a result of the dynamic nature of its coastal zones, of anthropogenic influences, such as coastal interventions and littoral occupation, and of the effects of climate change. The increase in the occurrence of extreme events, the weakening of river-sediment supplies, and the general acceleration of sea level rise (SLR) probably tends to aggravate coastal erosion on decadal time-scales. Describing vulnerability and risk patterns for energetic environmental actions is important for coastal planning and management to rationalize the decision-making process. To minimize negative effects, the various processes causing erosion must be understood to assess the possible prediction scenarios for coastal evolution in the medium to long term. This paper describes the application of a coastal (shoreline evolution) numerical model to a stretch of the Portuguese coast to determine the effects of various scenarios of wave action and SLR that might result from climate change over the next 25 years. We conclude that the effects of SLR are less important than changes in wave action. The numerical model was also applied in a generic situation to compare shoreline evolution with and without anthropogenic intervention.